The Effects of Staphylococcus aureus Cells Isolated from Albumen-Based Diet on the Growth and Survival of the Larvae of Clarias gariepinus - Fashina Bombata, H.A.; Bakre, S.; Ajayi, K.O.; Agboola, M. (Pakistan Journal of Nutrition, 2007)
Live organisms serve as ideal food for the early stages of fish and they have been found to have appreciable levels of micronutrients. Feeding fish larvae with formulated diets result in high mortality; the use of microbial cells as first food which, benefit the fish larvae by improving their intestinal balance is now being employed in hatcheries and have been shown to be successful. In this study, live cells of Staphylococcus aureus isolated from enriched albumen diet was fed to frys of Clarias gariepinus for Ten days to examine the growth response, survival and to determine the density of the live cells of the microbe that will have deleterious effects on the fry. This study has also shown that feeding with live cells of Staphylococcus aureus resulted in 80% survival of the catfish (Clarias species) larvae. The density of bacteria cells fed to the fish increased from 0.23 to 9.86x106 for the 10 days feeding trial. Growth interms of length and weight increased progressively for both commercial larvae feed and for those that received bacterial cell. However, there was a slight improved (P>0.05) growth in larvae fed with S. aureus.